Optimalisasi Tata Kelola Keuangan ZIS melalui Penerapan PSAK 109 pada LAZISKU KB PII: Pengabdian Kolaboratif - M. Zulflrman Hasibuan; Pancawati Hardiningsih (Jurnal Ragam Pengabdian, 2025)
Transparent and accountable financial governance is key to maintaining public trust in zakat institutions (LAZ). PSAK 109 serves as a guideline for sharia accounting in the management of zakat, infaq, and alms (ZIS), but its implementation is still limited in most community LAZs. This community service activity aims to assist LAZISKU KB PII in gradually implementing PSAK 109 to optimize ZIS's financial reporting. The implementation method includes initial assessment, training, technical assistance, and the preparation of financial SOPs based on PSAK 109. The results of the community service demonstrate a significant increase in management's understanding of the principles of PSAK 109, changes in the recognition and measurement of ZIS funds, and the development of an institutional commitment to maintaining consistent Sharia reporting. This activity demonstrates that a collaborative approach between academics and LAZs can be an effective strategy in strengthening the governance of Islamic social financial institutions